Pengaruh Daya Tarik Iklan, Citra Merek, Persepsi Harga Terhadap Niat Beli dan Keputusan Pembelian Netflix - Wendy Wendy; Meilisa Alvita (Jurnal Riset Ekonomi dan Akuntansi, 2024)
The Covid-19 pandemic, which began in 2020, has altered societal behavior patterns, including an increased reliance on online streaming services such as Netflix. This article analyzes the pandemic's impact on Netflix's services and the factors influencing post-pandemic user purchase intent. Through data and news quotations, this article highlights the significant growth of new Netflix users during the pandemic and the company's response to increased demand. Additionally, previous research on advertising appeal, brand image, and price perception is examined to understand how these factors affect user purchase intent. The research findings indicate that purchase decisions significantly influence user purchase intent for Netflix services. This finding is consistent with previous studies emphasizing the crucial role of advertising appeal in influencing purchase intent. Furthermore, a positive brand image has been proven to increase user purchase intent. However, in the context of price perception, no significant impact on purchase intent was found, underscoring that price does not significantly affect online customer purchase intent. In conclusion, to enhance user purchase intent and decision-making, it is important to consider advertising appeal and brand image aspects in Netflix's marketing strategy.